1991
DOI: 10.1103/physrevlett.66.1595
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for inhomogeneous swelling and deformation in statistical gels

Abstract: Polymer concentration correlations in a network swollen by a solvent are studied by small-angle neutron scattering. The network is made by statistical cross-linking of long chains in solution. At small scattering vectors, the intensity strongly increases upon swelling. Upon stretching, unusually oriented isointensity lines ("butterflies") are observed. These effects are well described by a model of fractal heterogeneities of cross-linking giving rise to nonhomogeneous swelling or deformation.PACS numbers: 64.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
148
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(162 citation statements)
references
References 8 publications
13
148
0
1
Order By: Relevance
“…The scattered intensity patterns at 42 1C were similar to the so-called butterfly pattern (or, more exactly, the abnormal butterfly pattern). 48 The scattering intensity contour had a lobe in the stretching direction. At 46 1C, a distinct peak appeared in both undeformed and deformed gels.…”
Section: Small-angle Neutron Scattering On Polymer Gels M Shibayamamentioning
confidence: 99%
See 1 more Smart Citation
“…The scattered intensity patterns at 42 1C were similar to the so-called butterfly pattern (or, more exactly, the abnormal butterfly pattern). 48 The scattering intensity contour had a lobe in the stretching direction. At 46 1C, a distinct peak appeared in both undeformed and deformed gels.…”
Section: Small-angle Neutron Scattering On Polymer Gels M Shibayamamentioning
confidence: 99%
“…35 Deformation mechanisms of polymeric systems have been studied by SANS. [47][48][49][50] Although SANS is a suitable means to study the deformation mechanisms of polymeric systems, chucking a polymer gel onto a stretching device is difficult in most cases because of its fragility. Geissler et al 51 used a mold with an elliptical hole and allowed a shrunken gel to swell anisotropically.…”
Section: Small-angle Neutron Scattering On Polymer Gels M Shibayamamentioning
confidence: 99%
“…Elles reflètent le plus souvent l'existence de fluctuations gelées (piégées par la réaction) de la répartition spatiale des points de réticulation [13]. On pourra aussi marquer (généralement avant réticulation) certaines des chaînes à partir desquelles le réseau est construit.…”
Section: Réseau Terminé : Quelle Structure ?unclassified
“…Therefore, under contact with an excess of solvent, the solvent is mainly absorbed by the regions between the clusters, and the gel swells heterogeneously. 1,2 Moreover, dynamic and static light scattering experiments on hydrogels have also revealed highly heterogeneous structures. [3][4][5] As demonstrated in the recent work of Oppermann and co-workers on polyacrylamide hydrogels, 5 the gel structure can be visualized as being built from densely cross-linked clusters (cross-link agglomerations) distributed in surroundings whose cross-link density is lower.…”
Section: Introductionmentioning
confidence: 99%
“…That one is indeed confronted with quite complex systems is well-documented experimentally. Thus, small-angle neutron scattering experiments 1,2 have shown that in statistical gels the local density of cross-links varies widely: The random arrangement of cross-links in the gel leads to local regions (clusters), whose cross-link density is much higher than on the average. Therefore, under contact with an excess of solvent, the solvent is mainly absorbed by the regions between the clusters, and the gel swells heterogeneously.…”
Section: Introductionmentioning
confidence: 99%